2009
DOI: 10.3389/neuro.11.022.2009
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, Distributed and Interactive Neuroimaging Data Analysis using the LONI Pipeline

Abstract: The LONI Pipeline is a graphical environment for construction, validation and execution of advanced neuroimaging data analysis protocols (Rex et al., 2003). It enables automated data format conversion, allows Grid utilization, facilitates data provenance, and provides a significant library of computational tools. There are two main advantages of the LONI Pipeline over other graphical analysis workflow architectures. It is built as a distributed Grid computing environment and permits efficient tool integration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
149
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 33 publications
0
149
0
Order By: Relevance
“…The incidence of posttraumatic seizures has been debated over the past 2 decades. 11 These studies focused on clinical seizure activity and did not use cEEG monitoring to define seizures. In contrast, we reported a 22% incidence rate of seizures when detailed, prospective cEEG monitoring of patients with TBI in the ICU was used.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of posttraumatic seizures has been debated over the past 2 decades. 11 These studies focused on clinical seizure activity and did not use cEEG monitoring to define seizures. In contrast, we reported a 22% incidence rate of seizures when detailed, prospective cEEG monitoring of patients with TBI in the ICU was used.…”
Section: Discussionmentioning
confidence: 99%
“…The LONI Pipeline is a workflow system developed by the Laboratory of Neuro Imaging (LONI) mainly for neuroimaging applications [3] [4]. It provides an efficient distributed computing solution to address common challenges in neuroimaging research, enabling investigators to share, integrate, collaborate and expand resources including data, computing platforms, and analytic algorithms.…”
Section: The Loni Pipelinementioning
confidence: 99%
“…This paper reports on a study on workflow reuse in labs that use a particular workflow system, the LONI Pipeline [3] [4]. The LONI Pipeline includes facilities for users to define subsets of workflows as "groupings" that may be reused by themselves and with others in new workflows.…”
Section: Introductionmentioning
confidence: 99%
“…42.8b . Utilizing the Pipeline environment developed by the Laboratory of Neuroimaging at UCLA ( http://pipeline.loni.ucla.edu/ ; [ 80 ] ) we have found that even without age-matching, anatomical brain regions could be mapped accurately. Beside the already available brain atlases, case-specifi c atlases can be developed for particular studies to improve computational performance.…”
Section: Anatomy-specifi C Lesion and Stem Cell Quantifi Cationmentioning
confidence: 99%